Plane-elliptical mirror furnace for crystal growth - Novaconi, S.; Boltosi, Al.; Baies, R.; Bartan, M.; Grozescu, I. (Functional Materials, 2004)
For single crystal growing in aggressive media, classical heating methods do not provide reliable results. In this study, we conceived and realized a system for radiant heating, by which the growth media is separated by the radiant and radiation focusing elements. The system is composed from an assembly of plane-elliptical mirrors with rod-shaped halogen lamps in the first focal centers and crucible as the second focal center. The growth medium being isolated, we could employ highly oxidant atmospheres and use crucibles made of dielectric oxide materials. The results obtained show a possibility to use the system to synthesize materials in aggressive media, as well as to configure the specific temperature gradients required by these processes. Классические методы нагрева не обеспечивают надежных результатов при выращивании монокристаллов в агрессивных средах. В этом исследовании нами разработана и реализована система для радиационного нагрева, с помощью которой достигается отделение ростовой среды от излучающих и фокусирующих излучение элементов. Система состоит из плоско-эллиптических зеркал с галогеновыми лампами стержневидной формы в первых фокальных центрах и тиглем во втором фокальном центре. Поскольку ростовая среда изолирована, возможно применение сильно окислительных сред и использование тиглей из диэлектрических оксидных материалов. Полученные результаты иллюстрируют возможность применения системы для синтеза материалов в агрессивных средах, а также для конфигурирования специальных систем градиентов темпера- Класичні способи нагрiвання не забезпечують надійних результатів при вирощу-вйнні монокристалів в агресивних середовищах. У цьому дослідженні розроблено та реалізовано систему для радіаційного нагріву, за допомогою якої досягається відділення ростового середовища від випромінювальних та фокусувальних елементів. Система складається з плоско-еліптичних дзеркал з галогеновими лампами стрижневої форми у перших фокальних центрах та з тиглем у другому фокальному центрі. Оскільки ростове середовище ізольоване, можливим є застосування сильно окиснювальних середовищ та використання тиглів з діелектричних оксидних матеріалів. Отримані результати посвідчують можливість застосування системи для синтезу матеріалів в агресивних середовищах, а також для формування спеціальних систем градієнтів температури, необхідних для таких процесів.